2018
DOI: 10.3390/insects9040135
|View full text |Cite
|
Sign up to set email alerts
|

Degassing Rhythms and Fluctuations of Geogenic Gases in A Red Wood-Ant Nest and in Soil in The Neuwied Basin (East Eifel Volcanic Field, Germany)

Abstract: Geochemical tracers of crustal fluids (CO2, He, Rn) provide a useful tool for the identification of buried fault structures. We acquired geochemical data during 7-months of continual sampling to identify causal processes underlying correlations between ambient air and degassing patterns of three gases (CO2, He, Rn) in a nest of red wood ants (Formica polyctena; “RWA”) and the soil at Goloring in the Neuwied Basin, a part of the East Eifel Volcanic Field (EEVF). We explored whether temporal relations and degass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…RWA nests were eight times more likely to be found within 60 m of known tectonic faults [12]. The results also showed that geogenic gases [13], rock formations with elevated Rn concentrations [14], fault-related CH4 emissions [15], volatile organo-halogens, alkanes and limonene [16] play key roles in the settlement of RWA nests. Physical phenomena such as tectonic stress variations in the subsurface, leading to highly mobile and oxidizing electronic charge carriers and formation of H2O2 that flow to the surface [17,18] may contribute to the survival of the colony.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…RWA nests were eight times more likely to be found within 60 m of known tectonic faults [12]. The results also showed that geogenic gases [13], rock formations with elevated Rn concentrations [14], fault-related CH4 emissions [15], volatile organo-halogens, alkanes and limonene [16] play key roles in the settlement of RWA nests. Physical phenomena such as tectonic stress variations in the subsurface, leading to highly mobile and oxidizing electronic charge carriers and formation of H2O2 that flow to the surface [17,18] may contribute to the survival of the colony.…”
Section: Introductionmentioning
confidence: 74%
“…Low to moderate seismicity (ML<4.2) showed historical events exceeding ML>5.0. Geochemical soil gas anomalies indicate crustal degassing along faults [13,16,45].…”
Section: Location and Tectonic Settings Of Study Areasmentioning
confidence: 99%
“…Tectonic movements could be an additional factor determining the number of nests. Local negative displacement rates are thought to slowly close pathways for geogenic gases, as observed at the four sites (Wolf, 2016;Berberich 2018bBerberich , 2022b. Since local negative displacement rates are nearly equal positive ascending rates in 09-Lis, this could explain the only slight loss of RWA nests in this area (Wolf 2016).…”
Section: Geobio-interactionsmentioning
confidence: 83%
“…Nest 2 ( F. polyctena ; partly sunlit, height: 0.50 m; diameter: 0.80 m; monitoring period 04-09/2010, Nest 3 ( F. polyctena ; partly sunlit, height: 0.50 m; diameter: 1.00 m; monitoring period 04-09/2012) and Nest 4 ( F. polyctena ; partly sunlit, height: 0.70 m; diameter: 2.20 m; monitored within the research project “GeoBio-Interactions” from 04-09/2016) were located at the Goloring site, an Iron-aged henge sanctuary (GDKE, 2018). In the past, the main selection criteria for the chosen RWA nests had been a seismically active area with degassing faults (Berberich et al, 2013; Berberich, et al 2018a; 2018b). For this reason, these 4 nests were the appropriate choices for studying ant activity patterns.…”
Section: Methodsmentioning
confidence: 99%
“…For this reason, these 4 nests were the appropriate choices for studying ant activity patterns. During our monitoring periods, long-term in situ data were acquired during field campaigns in which we also studied degassing of geogenic gases (He, Rn, CO 2 , CH 4 ) and tectonic processes associated with RWA nests in 2010, 2011, 2012(Berberich et al, 20132018a;2018b). Here, we use these long-term data and associated video footage of RWA colonies to assess ant activity and the possible influences of abiotic geophysical and meteorological processes.…”
Section: Red Wood-ant Nests and In Situ Continuous Monitoring Of Actimentioning
confidence: 99%